Comparison of Bacterial Leakage between 3 Different Root Canal Obturation Techniques in Oval Shaped Canals - Eshagh-ali Saberi; Shahram Shahraki; Sediqe Ebrahimipour; Anousheh Rashed Mohassel; Narjes Akbari; Majid Rezaei (Mashhad University of Medical Sciences, 2014)
Introduction: The purpose of this study was to evaluate the sealing ability of 3 obturation techniques in oval-shaped canals by bacterial leakage assessment. Methods: Sixty mandibular incisors with oval canals were selected after providing buccolingual and mesiodistal radiographs. The teeth were sectioned at a 10 mm distance from the apex. After instrumentation, the teeth were divided into 3 groups and the canals in the three groups were obturated with lateral condensation (G1), warm vertical condensation (G2) and thermoplasticized injectable gutta percha (G3). The teeth were exposed to human saliva. Observing the turbidity of the BHI broth for a period of 63 days the number of days required for the complete contamination of root canals was recorded. The data were analyzed using descriptive statistical methods and Kruskal-Wallis test with SPSS statistical software. Results: Warm vertical condensation (G2) needed a significantly greater average time for leakage than the two other methods. No significant differences were found between lateral condensations and thermoplasticized injectable G.P techniques. Conclusion: warm vertical condensation provides a better seal against bacterial leakage than lateral condensation and obtura II method in obturating oval-canals.